Mycobacterium-Inducible Nramp in Striped Bass (Morone saxatilis) - Burge, Erin J. (American Society for Microbiology, 2004)
In mammals, the natural resistance-associated macrophage protein 1 gene, Nramp1, plays a major role in resistance to mycobacterial infections. Chesapeake Bay striped bass (Morone saxatilis) is currently experiencing an epizootic of mycobacteriosis that threatens the health of this ecologically and economically important species. In the present study, we characterized an Nramp gene in this species and obtained evidence that there is induction following Mycobacterium exposure. The striped bass Nramp gene (MsNramp) and a 554-amino-acid sequence contain all the signal features of the Nramp family, including a topology of 12 transmembrane domains (TM), the transport protein-specific binding-protein-dependent transport system inner membrane component signature, three N-linked glycosylation sites between TM 7 and TM 8, sites of casein kinase and protein kinase C phosphorylation in the amino and carboxy termini, and a tyrosine kinase phosphorylation site between TM 6 and TM 7. Phylogenetic analysis most closely grouped MsNramp with other teleost Nramp genes and revealed high sequence similarity with mammalian Nramp2. MsNramp expression was present in all tissues assayed by reverse transcription-PCR. Within 1 day of injection of Mycobacterium marinum, MsNramp expression was highly induced (17-fold higher) in peritoneal exudate (PE) cells compared to the expression in controls. The levels of MsNramp were three- and sixfold higher on days 3 and 15, respectively. Injection of Mycobacterium shottsii resulted in two-, five-, and threefold increases in gene expression in PE cells over the time course. This report is the first report of induction of an Nramp gene by mycobacteria in a poikilothermic vertebrate.